Evolution of Risk Aversion over Five Years after a Major Natural Disaster - Ingwersen, Nicholas,Frankenberg, Elizabeth,Thomas, Duncan (National Bureau of Economic Research, 2023)
The impact of exposure to a major unanticipated natural disaster on the evolution of survivors' attitudes toward risk is examined, exploiting plausibly exogenous variation in exposure to the 2004 Indian Ocean tsunami in combination with rich population-representative longitudinal survey data spanning the five years after the tsunami. Respondents chose among pairs of hypothetical income streams. Those directly exposed to the tsunami made choices consistent with greater willingness to take on risk relative to those not directly exposed to the tsunami. These differences are short-lived: starting a year later, there is no evidence of differences in willingness to take on risk between the two groups. These conclusions hold for tsunami-related exposures measured at the individual and community level. Apparently, tsunami survivors were inclined to assume greater financial risk in the short-term while rebuilding their lives after the disaster
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Überschwemmung; Katastrophe; Konsumentenverhalten; Risikoaversion; Entscheidung unter Risiko; Pazifischer Ozean; Aceh; Sumatra; Indonesien; Consumer Economics: Empirical Analysis; Criteria for Decision-Making under Risk and Uncertainty; Microeconomic Analyses of Economic Development; Climate; Natural Disasters and Their Management; Global Warming